Wordwall in the Era of Information Openness: Strengthening Students’ Freedom of Expression - Prihatin, Anna Aisyah; Jatiningsih, Oksiana (IKIP Widya Darma Surabaya, 2026)
Objectives: This study aims to analyze the effectiveness of using Wordwall as a learning medium in strengthening students’ freedom of expression within the principles of Pancasila Democracy in junior high school students. Method: Using qualitative approach with a descriptive design, data were collected through survey, depth interview, observation, and documentation at State Junior High School 12 Surabaya. Results: The result show that Wordwall effective being implemented at State Junior High School 12 Surabaya with N-gain score 78% This research found that integrating Wordwall with Problem-Based Learning (PBL) significantly reinforces students’ abilities in several areas: 1) understanding of freedom of expression; 2) understanding of Pancasila democracy; 3) attitudes and behaviour in expressing opinions; 4) availability to analyze information; and 5) encouraging student freedom of expression. The challenges in this research were faced by both students and teachers, such as technical problems and limited internet connection. These outcomes collectively contribute to developing students’ democratic competence and their awareness of expressing opinions responsibly in accordance with Pancasila Democracy. Novelty: The novelty of this reach lie in interrogation of the use of technology in learning media, Wordwall, in the Framework of Pancasila democracy into freedom of expression learning, offering.